Pattern Of Different Eczema Among Outdoor Patients Attended Faridpur Medical College Hospital, Faridpur, Bangladesh - Ahmed, ARS; Islam, AKMS; Sarkar, SK; Mia, A (Faridpur Medical College Journal, 2011)
Eczematous dermatitis is very common in our country and all over the world. The aim of current study was to assess the burden, frequency and pattern of different eczema at outpatient department of Faridpur Medical College Hospital in the year 2009. Retrospective data were collected from medical records of patient. Patients of all ages & both sexes attending at the dermatology outpatient department of Faridpur Medical College Hospital in the year 2009 suffering from different eczema were included in this study. The frequency of eczema among patients attending at outpatient department of Faridpur Medical College Hospital was 12.8%, and the male to female ratio was almost 1:1. The most affected age group among patients was 0-5 years. Of all cases of eczema, 77.05% were endogenous and 22.52% were exogenous. The most common type of eczema was seborrhoeic dermatitis (27.17% of all cases), followed by contact dermatitis (20.00%) and Hand eczema (14.18%). Seborrhoeic dermatitis is commonest in young adult (21- 45 yrs), whereas atopic dermatitis is common in infant and children (0-10 yrs). Eczema is a public health problem in Faridpur, Bangladesh, and this necessitates prospective studies to determine its incidence and prevalence. Key words: Eczema; Atopic dermatitis; Faridpur DOI: 10.3329/fmcj.v5i2.6822 Faridpur Med. Coll. J. 2010;5(2):53-55